Attitudes and motivation in English language learning amongst multilingual university students in the Balearic Islands: the effect of the L1 and other influential variables. Issue 6 (3rd July 2019) - Moratinos-Johnston, Sofía; Ballester Brage, LLuís; Juan-Garau, Maria; Salazar-Noguera, Joana
ABSTRACT: Attitudes and motivation seem decisive in successful language learning (Dörnyei, Csizér, and Németh 2006. Motivation, Language Attitudes and Globalisation: A Hungarian Perspective . Clevedon: Multilingual Matters.). Research in Spanish multilingual contexts analysing the influence of the L1 on attitudes and motivation to learn foreign languages (FL) reveals mixed results. In the Basque country attitudes towards the FL were more positive amongst students with the majority language (Spanish) as their L1 than Basque speakers (Lasagabaster 2005. 'Attitudes towards Basque, Spanish and English: An Analysis of the Most Influential Variables.' Journal of Multilingual and Multicultural Development 26 (4): 296–316.). However, Loredo Gutiérrez et al. (2007. 'Language Use and Language Attitudes in Galicia.' In Multilingualism in European Bilingual Contexts: Language Use and Attitudes, edited by David Lasagabaster, and Angel Huguet, 40–65. Clevedon: Multilingual Matters.) in Galicia and Madariaga, Huguet, and Janés (2016. 'Language Attitudes in Catalan Multilingual Classrooms: Educational Implications.' Language and Intercultural Communication 16 (2): 216–34.) in Catalonia did not find significant differences among majority and minority language speakers. A later study (Lasagabaster 2016. 'The Relationship between Motivation, Gender, L1 and Possible Selves in English-Medium Instruction.' International Journal of Multilingualism 13 (3): 1–18.) targeting motivation in the Basque country determined that the L1 was not influential. This study analyses the effect that the L1 exerts on students' attitudes and motivation to learn English in the bilingual region of the Balearic Islands. Data from L1 Spanish/Catalan university students ( n  = 1, 021) was collected through a questionnaire. Statistical differences were found with Spanish L1 students displaying slightly more positive attitudes and motivation to learn English than Catalan L1 speakers, yet the effect size was small. This paper concludes that, in the Balearic Islands there are other factors determining attitudes and motivation such as linguistic self-confidence, cultural interest, international posture and instrumentality.